The improved efficacy of a fixed‐dose combination of fluticasone furoate and levocabastine relative to the individual components in the treatment of allergic rhinitis. Issue 8 (August 2015) - Murdoch, R. D.; Bareille, P.; Ignar, D.; Miller, S. R.; Gupta, A.; Boardley, R.; Zieglmayer, P.; Zieglmayer, R.; Lemel, P.; Horak, F.
Summary Background Allergic rhinitis (AR) is a common chronic disease, which has significant detrimental effect on well‐being and quality of life as well as substantial socio‐economic impact. Combination pharmacotherapy is utilized by 40–50% of patients to treat their symptoms. Objective To compare the effects of intranasal fluticasone furoate (FF)/levocabastine (LEVO) fixed‐dose combination (FDC) with each component alone on allergen‐induced nasal and ocular symptoms. Methods A randomized, double‐blind, placebo‐controlled, three‐way, incomplete block, cross‐over, proof‐of‐concept study in 71 patients with AR, evaluated FF 100 μg, LEVO 200 μg and FDC (FF 100/LEVO 200 μg), once daily via intranasal spray for 8 days. On days 1 and 8, total nasal symptom score (TNSS) and total ocular symptom score (TOSS) were assessed every 15 min during a 4‐h allergen exposure in the Vienna Challenge Chamber. The primary endpoint was Day 8 weighted mean TNSS. Results After 8 days, FDC resulted in both statistically and clinically significant reductions in mean TNSS compared with FF and LEVO alone [adjusted mean differences (95% CI): FDC vs. FF: −2.26 (−2.90, −1.62); FDC vs. LEVO: −2.57 (−3.21, −1.93)]. All active treatments were significantly superior to placebo [adjusted mean difference (95% CI) from placebo: FDC: −4.1 (−4.86, −3.34); FF: −1.84 (−2.66, −1.03); LEVO: −1.53 (−2.34, −0.72)]. Onset of action was rapid following FDC and LEVO treatment with an approximate two unit reduction in mean TNSS from pre‐dose levels by 30 min and 1 h. Mean TOSS was also reduced following all active treatments relative to placebo (range 0.6–0.8 unit reduction). All treatments were equally well tolerated. Conclusions and Clinical Relevance These results suggest that once daily FF/LEVO FDC could provide a clinical therapeutic advantage to existing standard monotherapies in the treatment of moderate‐to‐severe AR, and support progression to evaluation in larger phase III clinical studies.